DAYA DUKUNG LINGKUNGAN PERAIRAN TELUK EKAS UNTUK PENGEMBANGAN KEGIATAN BUDIDAYA IKAN KERAPU DALAM KARAM BA JARING APUNG - Majariana Krisanti; Zulhamsyah Imran (Jurnal Ilmu Pertanian Indonesia, 2006)
Grouper net cages culture in Ekas Bay, East Lombok, Nusa Tenggara Barat were carried out for public income improvement. The net cages culture also potentially waste generate that can be harmful for those activity itself. Waste potential study from net cages culture was conducted to obtain information about Ekas Bay carrying capacity for culture activity. The information consists of physical and chemical properties of water (salinity, water temperature, dissolved oxygen, pH, ammonia, nitrite, nitrate, turbidity, and depth) as primary and secondary data. According to ammonia and nitrate concentration, the net cages culture activities could not suit the carrying capacity of Ekas Bay. The cage culture activity should be organize therefore can be economically and ecologically profitable furthermore ecologically sustainable.